(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This article provides information about radiographic methods of liver and bile ducts. In particular: in the examination of the liver and bile ducts, ultrasound examination, computer tomography examination, and magnetic resonance imaging examination methods, the stages of examination, their benefits, and the harm they can cause and what effect they have in detail. data are cited.